Prioritizing rural roads projects in nort-eastern Tailand by analytical hierarcy process (AHP) - P. Cheonklang; I. Phummiphan; S. Horpibulsuk; M. Hoy (Lowland Technology International, 2018)
This paper presents the application of the Analytic Hierarchy Process (AHP) in rural roads prioritiation. The paper exhibits the concept and process of the plan for rural road development and application of multiple criteria decision analysis using AHP for prioritiing rural roads on a rational basis. Rural road network was grouped on strategic issues and strategies of Department of Rural Roads. There are three main factors to be used as an indicator to assess the importance of routes of each type of road: Transport and Traffic engineering, Accessibility and Other. The result of criteria weights was determined by Expert Choice software according to the AHP model. The results of weight factor analysis can be divided into 2 groups: the Transportation and Traffic Engineering dominant road (Logistics, Traffic Reduction and Countrys order Road) and the Accessibility dominant road (Tourism and Rural Area Accessibility Road). This study will be able to prioritie rural roads and allocate limited budget for development in the future. The master plan obtained from AHP application shows that this plan is consistent, and links with the country strategic plan under the Department of Rural Roads year 2017-2026, which is a longterm plan (10 years), and the Strategic Plan Framework Development of Rural Roads year 2017 - 2020, which is a medium-term plan (4 years). The main goal of the Rural Roads Development Plan in the area is to develop a rural road network to connect the Development of National Infrastructure and the Northeast Development Plan perfectly.